Description of two tadpoles and a key to the known larvae of the Bufo spinulosus group (Anura: Bufonidae) occurring in Peru - Aguilar, César (2004)
The tadpoles of Bufo arequipensis and Bufo cophotis are described. No external larval character studied allowed the distinction between the tadpoles of the nominal species B. arequipensis, B. flavolineatus and B. trifolium. The tadpole of B. limensis differs from the ones of B. flavolineatus and B. trifolium by the presence of a small gap in the second anterior tooth row and a 2(2)/3[1] labial tooth row formula (LTRF). The tadpole of B. cophotis differs from B. limensis, B. flavolineatus and B. trifolium larvae by showing the highest part of the tail in its posterior end, a dark brown coloration in the body and tail, and a 2(2)/3(1) LTRF. An identification key for the known Peruvian tadpoles of the spinulosus group is provided.